Factors affecting consumers’ satisfaction based on mall attributes in Seremban / Nur Batrisyia Aliah Yusmar and Najma Azman - Yusmar, Nur Batrisyia Aliah; Azman, Najma (2023)
Malaysia's wholesale and retail sector continues to play an important role in the economy. Shopping malls regularly disregard how crucial it is in offering customers pleasant shopping experiences in order to achieve economic prosperity. It turns out, connection between the shopping mall and its features and service must take place in order to deliver efficiency, offer significant value to the business, and fulfil the expectations of customers. This paper suggests different kinds of mall attributes that shoppers might enjoy in a pleasant way. This study aims to identify the factors influencing the customers’ satisfactions towards shopping mall attributes and to determine the level of customers’ satisfaction towards the shopping mall attributes. There were 204 respondents involved in this research, representing the shopping mall visitors in Seremban. The results were analysed to determine the study's significance and from the findings it is clear that each characteristic of the shopping mall must be taken into account as a reason people prefer to visit one shopping mall over another. Most visitors from selected shopping malls are satisfied with some factors. The degree of customers’ satisfaction also somehow affected the customers’ loyalty. Several suggestions have been made in this study as to provide more information towards mall developers and management about which factors influence the customer satisfaction which can lead to the success in growing of the shopping mall in Seremban.